2022
DOI: 10.1371/journal.pone.0259609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture on the expression of hypothalamic neuropeptide Y and ghrelin in pubertal rats with polycystic ovary syndrome

Abstract: Background Polycystic ovary syndrome often starts in puberty, and its pathogenesis is not clear. This study aimed to explore the pathogenesis of pubertal polycystic ovary syndrome (PCOS) and assess the therapeutic effect of electroacupuncture on pubertal PCOS. Methods Dihydrotestosterone (DHT) was used to induce rat models of pubertal PCOS. pubertal rats with PCOS were randomly divided into a model group (M), an electroacupuncture group (EA), and a sham acupuncture group (SA). Age-matched normal rats were re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It can improve the disordered estrous cycle, ovarian tissue morphology, and hormone levels of FSH, LH, and E 2 in rats with PCOS. [33][34][35][36] Concurrently, it also has a similar therapeutic effect on the improvement of symptoms in PCOS mice such as C57BL/6J mice and female mice of the Institute for Cancer Research. 37,38 In addition, the mechanism of electroacupuncture improving the symptoms of PCOS rats has also been developed.…”
Section: Electroacupuncturementioning
confidence: 93%
See 1 more Smart Citation
“…It can improve the disordered estrous cycle, ovarian tissue morphology, and hormone levels of FSH, LH, and E 2 in rats with PCOS. [33][34][35][36] Concurrently, it also has a similar therapeutic effect on the improvement of symptoms in PCOS mice such as C57BL/6J mice and female mice of the Institute for Cancer Research. 37,38 In addition, the mechanism of electroacupuncture improving the symptoms of PCOS rats has also been developed.…”
Section: Electroacupuncturementioning
confidence: 93%
“…Cong et al 33 also clarified the ability of electroacupuncture to resist the effects of PCOS by inhibiting endoplasmic reticulum stress-mediated apoptosis and autophagy of ovarian granulosa cells. In addition, electroacupuncture can also improve the reproductive characteristics of PCOS rats by regulating hypothalamic neuropeptide Y and growth hormone levels, 34 regulating Alas2-mediated apoptosis and mitochondrial function, 39 and regulating kisspeptin-GnRH/LH pathway through androgen activity attenuation. 35 Chen et al 40 showed that electroacupuncture also had a certain promoting effect on ovarian function and menstrual cycle of POF mice.…”
Section: Electroacupuncturementioning
confidence: 99%
“…This elevated hypothalamic GnRH output is likely to stem in part from a change of the metabolic state of the body. Neuropeptide Y (NPY), ghrelin (GHRL), galanin (GAL), and galanin-like peptide (GALP) have been proposed as candidates conveying metabolic status to the GnRH neuronal network in animals [8]. GALP is a recently identified hypothalamic peptide, localized…”
mentioning
confidence: 99%